2014
DOI: 10.1071/an13150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of organic and inorganic selenium supplementation during late pregnancy on colostrum and serum Se status, performance and passive immunity in Merghoz goats

Abstract: This study was conducted to determine the effects of organic and inorganic selenium (Se) supplementation during late pregnancy on serum Se status, colostrum, performance and passive immunity in Merghoz goats in Iran. Thirty Merghoz goats (30 ± 3 kg) were given the same basal diet containing 0.11 mg Se/kg DM and were randomly allocated to one of three dietary treatments in a randomised complete block design. Four weeks before the expected kidding, the basal diets were supplemented with 0 (control), 0.3 mg Se/he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
1
2
0
1
Order By: Relevance
“…In agreement with the present study, the addition of Se to the maternal diet increased Se concentration in serum and colostrum of mares and goats [ 40 , 41 ]. Juniper et al [ 13 ], in agreement with the present study, found a significantly higher selenium concentration ( p < 0.001) in the whole blood of lambs after the addition of selenium yeast to their diet.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with the present study, the addition of Se to the maternal diet increased Se concentration in serum and colostrum of mares and goats [ 40 , 41 ]. Juniper et al [ 13 ], in agreement with the present study, found a significantly higher selenium concentration ( p < 0.001) in the whole blood of lambs after the addition of selenium yeast to their diet.…”
Section: Discussionsupporting
confidence: 92%
“…Selenium placental transfer was demonstrated by De Toledo and Perry (1985) and Stewart et al (2012) and fetal selenium concentrations have been shown to be greater (Stewart et al, 2012) than corresponding maternal selenium concentrations. Addition of Se to the maternal diet increased Se concentration in both serum and colostrum (Phipps et al, 2008;Slavik et al, 2008;Karren et al, 2010;Kachuca et al, 2013). Hefnawy and Tortoro-Perez (2010) explored the effects of addition of selenium in the diets of sheep before and after birth and concluded that prepartum addition of Se played on active role in maintaining optimal plasma selenium level, while postpartum addition of Se ensured the continuation of milk.…”
Section: Discussionmentioning
confidence: 99%
“…Smrt kod trovanja selenom nastaje usled edema pluća ili ciroze jetre 45 . Kod previsokog unosa selena dolazi do redukcije cinka u organizmu i poremećaja odnosa cink/bakar i njihove antioksidantne aktivnosti 46 .…”
Section: Zaključakunclassified